2013
DOI: 10.1002/ijc.28262
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and insulin‐like growth factor 1 synergistically promote the development of lung adenocarcinoma in mice

Abstract: Estrogen receptor (ER) and insulin‐like growth factor‐1 receptor (IGF‐1R) signaling are implicated in lung cancer progression. Based on their previous findings, the authors sought to investigate whether estrogen and IGF‐1 act synergistically to promote lung adenocarcinoma (LADE) development in mice. LADE was induced with urethane in ovariectomized Kunming mice. Tumor‐bearing mice were divided into seven groups: 17β‐estradiol (E2), E2+fulvestrant (Ful; estrogen inhibitor), IGF‐1, IGF‐1+AG1024 (IGF‐1 inhibitor),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 50 publications
8
52
0
Order By: Relevance
“…We have shown that the tumor multiplicity and the inflammatory response were more obviously by E2 treatment, indicating that E2 can strongly potentiate inflammation and tumorigenesis induced by NNK (Table 2). These results are consistent with previous studies showed that estrogen not only promotes the malignant development of breast cancer, but also acts on non-target organs, including lung cancer through various molecular mechanisms [21,22]. In addition to the solitary effect of estrogen, females exposed to other environmental chemicals such as benzo [a]pyrene that may interfere with the physiological functions of estrogen leading to increasing susceptibility of cancers [23][24][25].…”
Section: Discussionsupporting
confidence: 81%
“…We have shown that the tumor multiplicity and the inflammatory response were more obviously by E2 treatment, indicating that E2 can strongly potentiate inflammation and tumorigenesis induced by NNK (Table 2). These results are consistent with previous studies showed that estrogen not only promotes the malignant development of breast cancer, but also acts on non-target organs, including lung cancer through various molecular mechanisms [21,22]. In addition to the solitary effect of estrogen, females exposed to other environmental chemicals such as benzo [a]pyrene that may interfere with the physiological functions of estrogen leading to increasing susceptibility of cancers [23][24][25].…”
Section: Discussionsupporting
confidence: 81%
“…Similar to Med, in human lung cancers, ER␤ and IGF1R expression levels are positively correlated, and increased levels of their expression are associated with poor prognosis (64). In ER␤-positive/ER␣-negative nonsmall cell lung cancer cells E2 acts via ER␤ to increase IGF1R expression and signaling, and in a mouse model of lung adenocarcinoma E2 promotes tumor development through this mechanism (64,65). It is notable that ER␣ is typically not expressed, or expressed at very low levels, in both Med and lung cancer where the tumor promoting effects of E2 increases IGF1R expression and signaling via ER␤, thus raising the possibility that ER␣ status might be a central determinant in defining the tumor growth potential of ER␤.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, in some studies ERβ was found to be the main receptor mediating the proliferative effects of estrogens in lung cancer cells [18]. Furthermore, ERβ appears to be involved with insulin-like growth factor-1 receptor (IGF-1R) in a synergistic promotion of lung adenocarcinoma development in murine models [19]. On the other hand, other studies indicate that ERβ may have prognostic value, since its overexpression appears to be a positive prognostic marker in stage II and III non-small cell lung cancer (NSCLC) patients [20], whereas its absence, together with the presence of ERα, was associated with a poorer prognosis in patients affected by the same type of cancer [21].…”
Section: Potential Clinical Applications Of Erα and Erβ Modulatorsmentioning
confidence: 99%